Class 3 semaphorins: physiological vascular normalizing agents for anti‐cancer therapy. (19th January 2013) - Serini, G.; Bussolino, F.; Maione, F.; Giraudo, E.
Abstract Findings from preclinical and clinical studies show that vascular normalization represents a novel strategy to enhance the efficacy of and overcome the acquired resistance to anti‐angiogenic therapies in cancer. Several mechanisms of tumour vessel normalization have been revealed. Amongst them, secreted class 3 semaphorins (Sema3), which regulate axon guidance and angiogenesis, have been recently identified as novel vascular normalizing agents that inhibit metastatic dissemination by restoring vascular function. Here, we discuss the different biological functions and mechanisms of action of Sema3 in the context of tumour vascular normalization, and their impact on the different cellular components of the tumour microenvironment.